Research on the Coupling between the Development Level and Efficiency of Green Agriculture in China - Pan, Haoren; Jiang, Ling; Tang, Meimei (International Journal of Global Economics and Management, 2024)
Accurately measuring the green development status of China's agriculture is of great significance for promoting the transformation of agricultural development modes, promoting green agricultural development models, and forming a sustainable modern agricultural production system. The purpose of this study is to provide scientific reference and practical guidance for the implementation of China's agricultural modernization and sustainable development strategy through in-depth analysis of the coupling between the development level of green agriculture in China and production efficiency. It has important theoretical and practical value for promoting the construction of agricultural ecological civilization. This article first analyzes the current situation and development efficiency of green agriculture in China. Then, the coupling between the development level and efficiency of green agriculture in China was analyzed. Finally, propose countermeasures and suggestions.